2014
DOI: 10.1080/00140139.2014.909949
|View full text |Cite
|
Sign up to set email alerts
|

Using team cognitive work analysis to reveal healthcare team interactions in a birthing unit

Abstract: Cognitive work analysis (CWA) as an analytical approach for examining complex sociotechnical systems has shown success in modelling the work of single operators. The CWA approach incorporates social and team interactions, but a more explicit analysis of team aspects can reveal more information for systems design. In this paper, Team CWA is explored to understand teamwork within a birthing unit at a hospital. Team CWA models are derived from theories and models of teamworkand leverage the existing CWA approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…Effken et al 2001, Miller 2004, Sharp and Helmicki 1998. Other applications include the development of decision support tools (Hajdukiewicz et al 2001;Effken et al 2011), understanding of contributors to inpatient falls (Lopez et al 2010), inpatient medication management system (Pingenot et al 2009) and team working (Ashoori et al 2014). …”
Section: Work Domain Analysis (Wda)mentioning
confidence: 99%
“…Effken et al 2001, Miller 2004, Sharp and Helmicki 1998. Other applications include the development of decision support tools (Hajdukiewicz et al 2001;Effken et al 2011), understanding of contributors to inpatient falls (Lopez et al 2010), inpatient medication management system (Pingenot et al 2009) and team working (Ashoori et al 2014). …”
Section: Work Domain Analysis (Wda)mentioning
confidence: 99%
“…Other applications include, for example, analysis of complex socio-technical systems (Stanton & Bessell 2014), analysis of team cognitive work (Ashoori et al 2014), and development of decision aids in healthcare (Dhukaram & Baber 2015). The decision ladder also has descriptive value, especially when used as a template with which to analyse verbal protocols (Vicente 1999).…”
Section: Decision Process Structurementioning
confidence: 99%
“…In their study of medical teams using team Cognitive Work Analysis, Ashoori et al (2014) suggested that team strategies could be assessed against four categories:…”
Section: Team Strategies Analysismentioning
confidence: 99%
“…Ashoori et al (2014) found that team Work Domain Analysis provided information about shared boundary objects, shared elements of the information space in surgical teams. In support of the findings of Ashoori et al (2014), this study also The Work Domain Analysis also identified that the agencies share many of the same boundary objects in order to achieve their tasks. Shared boundary objects need to be adaptable to all traffic incident management requirements and seamless across agencies.…”
Section: Team Work Domain Analysis Findingsmentioning
confidence: 99%
See 1 more Smart Citation